Resource Management on Ojibwe Ceded Territory: Race, Politics and Collaboration - Farah Benramdane (Transatlantica)
The mining sector has played a key part in redefining the relationship between Ojibwe tribes and the state of Wisconsin. The reaffirmation of treaty rights by the District court in 1983, and the subsequent spearfishing controversy that divided the state between anti-treaty and pro-treaty protesters put the issue of reserved rights at the forefront of the anti-mining movement that developed in the 1990s. The anti-treaty movement, which relied on misleading information regarding the dangers of spearfishing for the fish population, lost the support of many of its members when it became evident that metallic mining constituted the most pressing issue, threatening the water quality of the lakes surrounding the projects. The 1983 Voigt ruling, which reaffirmed Ojibwe reserved rights, meant that state and federal agencies were required to guarantee the tribes access to uncontaminated fish, game and water. When Exxon applied for a permit to mine for the Crandon project, sport fishermen who had vehemently opposed off-reservation fishing, became aware of the legal value of treaty rights to oppose the mine. Drawing in part from the works of geographer Zoltán Grossman and sociology professor Al Gedicks, this article will show that the reaffirmation of reserved rights, and the spearfishing controversy that divided Northern Wisconsin, participated in the emergence of one of the first environmental/Indigenous alliances in the United States, and the creation of grassroots rural organizations, reshaping interracial and intergovernmental relations in Wisconsin.